早期都市文化语境下的华语语系电影明星 ：以白云为个案 = Sinophone cinema stars in early urban cultural context : a case study on Bai Yun - 王思扬 Wang, Siyang (2016)
电影明星的诞生有赖于大众媒体的打造和都市文化的兴起。作为被公众凝视和文化消费的对象，他们一方面是当时政治、经济和社会生活的折射；另一方面，又凭借自身巨大的社会影响力，成为文化生产的重要力量。近年来，中国电影明星研究逐渐引起学者注意，并有不少学者做了较有价值的研究，但关于二十世纪早期华语电影明星的研究多集中于女明星，而处在中国边缘的方言电影和中国以外的华语语系电影明星则常常被忽略，难以在“中国中心主义”的传统电影史中获得一席之地，这就为本研究提供了较大的空间。 本文选择以早期华语电影明星白云（1916～1982）为个案，借用“华语语系”和“明星研究”理论，透过当时的报纸、电影杂志、画报及有关回忆录等史料，对白云的明星生涯作了全面、系统的梳理。笔者将白云定义为“华语语系”明星，不仅是因为白云新马生长的华人身份，更是由于他往返于上海、香港、台湾之间的波折而复杂的演艺生涯。白云出生于马来亚，成长于新加坡，成名于 1940 年代的上海影坛，1950 年代红遍香港影坛和全球华人世界，但却“失踪”于华语电影史。本研究着力于联系当时的社会历史和早期华语电影产业发展背景，着重从时间和空间、银幕形象和社会形象等多方位、多视角，系统的探讨作为华语语系电影明星的白云的明星形象和其身上背负的时代痕迹。笔者希望通过对白云的分析研究，可以使我们以一个全新的视角，重新关照早期华语语系电影明星的生存状态，进而更加深入的认识早期华语语系电影产业和都市文化语境，乃至早期华语电影发展过程中的城际互动。 This thesis take Bai Yun(1916-1982) as an example, try to use Sinophone Studies and Star Studies in the research, and intend to introduces Bai Yun’ s life stories and background detailedly. All of the above are based on the historical materials such as newspapers, cinema magazines, pictorial, memoirs, etc. Bai Yun is defined as Sinophone Stars, not only because he was a Chinese in Singapore and Malaya, but also because of his complicated acting career between Shanghai, Hong Kong and Taiwan. Bai Yun was born in Malaya and grew up in Singapore, he made a name for himself in Shanghai moviedom in the 1940s, and was popular in Hong Kong moviedom and Chinese-speaking world in the 1950s, but missing in the history of Chinese-language Cinemas. This analysis is combined with the social history and film industry background of that times, it is also analyze the characteristic of early Sinophone male stars and the im-print of the times from the multi-perspective of time, space, screen image and social image. Through the analysis of Bai Yun, the author wishes to have a better understanding of ear-ly Sinophone cinema industry and urban culture, as well as the interaction between dif-ferent cities in the early development of Sinophone cinema industry.